2022
DOI: 10.3390/su14042366
|View full text |Cite
|
Sign up to set email alerts
|

Fortuitous Alignment: The Royal Botanic Gardens, Kew and the Sustainable Development Goals

Abstract: The Sustainable Development Goals (SDGs) are aimed at improving human well-being at a global scale, whilst enhancing and preserving global biodiversity. Recently, botanic gardens worldwide have become more conservation focused, and gardens are increasingly influential in scientific roles that address both biodiversity loss and human well-being—particularly in urban areas. As the Royal Botanic Gardens, Kew (Kew) launched its new Manifesto for Change in 2021, this paper outlines how the organisation currently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The process started with a review of the 17 goals, 169 targets and 232 indicators. In line with previous research, we found that most indicators were difficult to apply to organizations [22]. Therefore, the UN-SDG indicators were not included in our evaluation framework, and garden activities were assessed only for the goals and targets.…”
Section: Methodsmentioning
confidence: 54%
“…The process started with a review of the 17 goals, 169 targets and 232 indicators. In line with previous research, we found that most indicators were difficult to apply to organizations [22]. Therefore, the UN-SDG indicators were not included in our evaluation framework, and garden activities were assessed only for the goals and targets.…”
Section: Methodsmentioning
confidence: 54%
“…The dominance of conservation and biodiversity themes in the research of botanical gardens aligns with their historical role as custodians of plant diversity. This is evident in the growing trend among botanical gardens worldwide to prioritize conservation efforts, particularly in preserving rare and endangered plant species and conserving biodiversity [12,64]. International agendas, such as the International Agenda for Botanic Gardens in Conservation and the Global Strategy for Plant Conservation, have played a significant role in shaping the conservation-oriented approach of botanical gardens [64,65], underscoring the importance of plant conservation, restoration, and reintroduction programs.…”
Section: Discussionmentioning
confidence: 99%
“…As such, TSR aligns closely with the principles and objectives of the 17 United Nations' SDGs [30][31][32][33][34], which aim to stimulate cross-sectoral, collaborative partnerships in tackling complex global challenges related to poverty, inequality, climate change, and environmental degradation [35]. This commentary paper considers the application of TSR approaches within the context of botanic garden tourism development to promote the SDG for good health and well-being while considering opportunities surrounding plant awareness disparity (PAD) [36] and the alignment of a variety of SDGs [21,34,[37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The present commentary concludes with suggested research priority areas where TSR approaches could catalyze service innovations that leverage botanic garden tourism. It is intended that such considerations and proaction improve accessibility, mindfulness, visitor behavior and epistemological change in botanic garden guests and partnerships, visitor economy, visitor experience, social value, and community health outcomes as well as ultimately contribute to meeting SDGs and the sector's strategic vision, mission, aims, and objectives [4,6,[8][9][10]21,34,39,40,43,44,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%